Competitive interactions between halothane and isoflurane at the carotid body and TASK channels - Pandit, JJ; Huskens, N; O'Donohoe, PB; Turner, PJ; Buckler, KJ (Lippincott, Williams and Wilkins, 2020)
Background: The degree to which different volatile anesthetics depress carotid body hypoxic response relates to their ability to activate TASK potassium channels. Most commonly, volatile anesthetic pairs act additively at their molecular targets. We examined whether this applied to carotid body TASK channels.